2019
DOI: 10.1007/s10776-019-00421-2
|View full text |Cite
|
Sign up to set email alerts
|

Precision of RSS-Based Localization in the IoT

Abstract: Currently, the most popular indoor geolocation technique used in smart device is the RSS-based Wi-Fi localization. The general accuracy of Wi-Fi localization in around 10-15 m. To improve this accuracy in indoor areas, site survey is commonly used to collect a signature data base. With the emergence of smart buildings and the IoT to connect the sensors for the smart building, a number of low power sensor devices with diversified power levels will be deployed in the building. The radiated RSS from these devices… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…In addition, there is another major problem with the location of the information signals source (RFID tags) because the antenna cannot locate the tags by itself. The location of the wireless source has drawn considerable attention in the last two decades [ 25 , 26 ]. Various localization methods, i.e., energy-based localization of the received signal strength (RSS) or the received signal strength difference (RSSD), allow for simple implementation compared to other traditional technologies, such as time of arrival (ToA), time difference of arrival (TDoA), direction of arrival (DoA), angle of departure (AoD), and angle of arrival (AoA) [ 27 , 28 , 29 , 30 , 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there is another major problem with the location of the information signals source (RFID tags) because the antenna cannot locate the tags by itself. The location of the wireless source has drawn considerable attention in the last two decades [ 25 , 26 ]. Various localization methods, i.e., energy-based localization of the received signal strength (RSS) or the received signal strength difference (RSSD), allow for simple implementation compared to other traditional technologies, such as time of arrival (ToA), time difference of arrival (TDoA), direction of arrival (DoA), angle of departure (AoD), and angle of arrival (AoA) [ 27 , 28 , 29 , 30 , 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…It can be shown that the precision of Wi-Fi positioning in a typical building (e.g. WPI's Atwater Kent Laboratory), with three Wi-Fi APs in 90% of locations is better than 15 meters, while with only eight randomly distributed IoT devices in that floor this precision comes close to two meters [21], [22]. In practice, design of such systems is practical because all devices measure their RSS and they are connected to the Internet, therefore they can pass that information to a positioning database to enhance the precision of positioning.…”
Section: ) Future Directions Of Wpsmentioning
confidence: 99%
“…Initial approaches to deal with the problem of radiation patterns from a functional perspective discuss using onboard compasses [11], [10], this approach can provide corrections when performing self-localisation or when working cooperatively with infrastructure. However, as is the case with all data fusion approaches [12], [13], [14], [15], [16], the required information is not always available. It may be undesirable to rely on information from a device under the control of an external entity, particularly in a security context where an adversary may spoof the onboard data.…”
Section: Introductionmentioning
confidence: 99%